Un acercamiento a una perspectiva ecológica en la educación - William Delgado-Montoya (Universidad Nacional, Costa Rica, 2011)
Proposal of an approach to education from an ecological perspective. This perspective is understood as the adaptation and adjustment between a growing and active human being and the natural and social scenarios that surround. Education is seen as a social structure favoring adaptation mechanisms by means of explaining, predicting, interpreting and transmitting social culture and practices, and by configuring the different scenarios where teaching-learning principles take place. Thus, the classroom becomes a place that fosters interactions among individuals (teachers and students). As a result, an ecological perspective in education is an opportunity to develop research that values cultural animation, students' learning context, and the ever changing human interaction in order to promote an altruistic search for solutions to the various problems encountered.